Effects of curing on the hydro-mechanical behaviour of cement-bentonite mixtures for cut-off walls. (20th June 2023) - Flessati, Luca; Vecchia, Gabriele Della; Musso, Guido
Highlights: Cement-bentonite mixtures hydro-mechanical properties improve with curing time and curing conditions. The hydraulic behaviour of cement-bentonite mixtures can be reproduced with a Kozeny-Carman like equation. The mechanical behaviour of cement-bentonite mixture can be reproduced with a strain hardening elastic plastic constitutive law conceived by combining models commonly employed for clays and for sands. Abstract: Cement-bentonite cut-off walls are commonly employed in geoenvironmental applications to limit ground water flow and pollutant transport. The wide diffusion of this artificial material in the current practice is not only due to its low permeability, but also to its simplicity of use. In this paper, experimental evidences about the role of curing on the hydro-mechanical behaviour of cement-bentonite mixtures are presented. Different curing times and curing conditions (representative for either water saturated or hydrocarbon polluted soils) have been considered, and their effects on both hydraulic conductivity and mechanical response in oedometer and triaxial conditions have been assessed. A unified hydro-mechanical framework, accounting for the changes of material fabric occurring with curing time and environment, is formulated. The hydraulic conductivity is very well predicted by a Kozeny-Carman like equation, whereas the mechanical behaviour is finely reproduced via an enhanced elastic–plastic constitutive model.